Multivariate Statistical Analyses of Fluoride and Other Physicochemical Parameters in Groundwater Samples of Two Megacities in Asia: Lahore and Sialkot - Saadia Rashid Tariq (Journal of Chemistry)
The present study was carried out to evaluate the current status of contaminants and their sources in groundwater samples collected from Lahore and Sialkot. A total of 93 samples were collected from different localities of Lahore and Sialkot and analyzed for the determination of various physicochemical parameters. The results of the study revealed that mean fluoride and chloride contents of water samples from Lahore were higher than the values recommended by Pak-EPA and WHO whereas the mean nitrate and sulphate levels of these samples were well within the limits. The order observed for these physicochemical parameters from Lahore was Cl− > alkalinity > SO4-2 > NO3- > F−. All the observed physicochemical parameters for water samples from Sialkot were found to be greater than those of Lahore, due to a more intensive industrial activity in Sialkot. The correlation study revealed the strongest correlation among conductance and alkalinity in samples from both cities. Fluoride and sulphate were found to be positively correlated in samples from Lahore and negatively correlated in samples from Sialkot. Multivariate analysis in terms of principle component analysis and cluster analysis furnished information about the sources of various parameters in groundwater samples.